Does corruption affect public debt in developed and developing countries? An empirical analysis - Chan, Kha Man; Cheng, Poh Choo; Chong, Mei June; Loh, Hui Yuan; Tang, Swee Ping (2019)
While corruption on public debt has been widely investigated in many different countries, it is often overlooked some specific countries in the world. However, corruption was the main issue that affect public debt in the country and bring negative impact to the country’s economy. Hence, this study aimed at examining the influence of corruption and other control variable on public debt in developed and developing countries. GMM was apply to investigate the result of corruption and other control variable on public debt. The result indicate corruption has a significant and positive impact on public debt.